Theories in and of Mathematics Education Theory Strands in German Speaking Countries - Bikner-Ahsbahs, Angelika; Vohns, Andreas; Schmitt, Oliver; Bruder, Regina; Dörfler, Willi (ICME-13 Topical Surveys, 2016)
VI, 51 p. 10 illus.